Bangladesh-China-India-Myanmar Economic Corridor (BCIM-EC) Options for Participating Countries - Awais; Azhar Ahmad (National University of Modern Languages (NUML), Islamabad, 2023)
This study deals with Bangladesh-China-India-Myanmar Economic Corridor (BCIM-EC), one of six economic corridors of Belt & Road Initiative (BRI) designed by China in 2013 to establish regional connectivity with South Asian countries and Indian Ocean. The countries of BCIM-EC had a traditional interaction in the socio-economic and cultural fields under Bangladesh-China-India-Myanmar (BCIM) forum that existed long before BRI since 1999. After the launch of BRI, the BCIM forum was brought under the umbrella of BRI which was objected by India due to its reservations towards BRI. The project got set back since the establishment of Modi's government in India which ultimately halted the opportunity of development and integration of the region. This study argues that BCIM-EC provides the best opportunity for its participating countries to address their socio-economic problems through launching various infrastructural projects with the financial help of China. To explore the potentials of this corridor, qualitative research methods have been used and data collected from various articles, research papers, statements of leaders of participating countries and opinion of scholars of relevant fields. This research is conducted mainly under two theories i.e. the Complex Interdependence and Prospect Theory which helped in studying the potentials of this corridor for the participating countries on one hand and exploring the possible options to execute it successfully on the other hand. The findings of the study state that the BCIM-EC has great potentials for the participating countries but their geostrategic gains and losses must not be counted the same. It also gives certain options to put the BCIM-EC on track through misusing India for the time being by launching Bangladesh China Myanmar Economic Corridor (BCM-EC).